ANALISIS PERSPEKTIF KONSUMEN TERHADAP PRODUK OLYMPIC DI TOKO OLYMPIC MEUBEL PASIR PENGARAIAN KABUPATEN ROKAN HULU - -, Jeprizal (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2016)
This research aim to to measure and know in perpectively of consumer to product of Olympic inshop of Olympic meubel pasir pengaraian of Sub-Province of Rokan Hulu;Upstream. Methodintake of data in this research is observation method, kuisioner, shop archives and document, thisresearch is conducted in Shop of Olympic Meubel Pasir Pengaraian Sub-Province of Rokan Hulu,Upstream, as for becoming population in this research is all shop consumer of olympic meubelwith technique intake of Accidental sampling, that is technique intake of sampel incidentally withamount of sampel 35 people. Instrument at this research is validity test and test of reliabilitas, andtechnique analyse the data of is by using TCR. At indicator satisfaction of cutomer categorizeenoughly (72,6%), at cutomer retention indicator stay in good enough category ( 72,6 %), atindicator of akuisisi consumer categorize goodly ( 88 %), at [cutomer/ client] profitabilityindicator categorize very good ( 95,3 %), at market compartment indiator categorize goodly ( 80%), at product attribute indicator categorize goodly ( 88 %), at relation indicator with cutomercategorize good enoughly ( 78 %), and at indicator concerning reputation and image categorizegoodly ( 81,3%).Keywords: Ad For Consumer, Product of Olympic..